Meningkatkan Status Gizi Ibu Hamil melalui Edukasi dan Pemberian Makanan Tambahan (PMT) dalam Rangka Pencegahan Kekurangan Energi Kronis (KEK) - Febrianti, Nuristha; Hardianti, Hardianti; Putri, Puput (Al-DYAS, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a nutritional issue that poses serious risks to pregnancy and fetal development, such as low birth weight (LBW), prematurity, and stunting. In the working area of Anuntodea Tipo Health Center, cases of pregnant women with upper arm circumference (MUAC) < 23.5 cm, an indicator of CED, are still being reported. This study aims to improve the nutritional status of pregnant women at risk of CED through nutrition education and the provision of locally sourced supplementary food (PMT). A quasi-experimental method with a pre-test and post-test design without a control group was employed. The subjects consisted of 20 pregnant women with CED who participated in weekly nutrition education sessions and received PMT for 12 weeks. Body weight and MUAC measurements were taken before and after the intervention and analyzed descriptively and using paired t-tests. The results showed an average weight gain of 1.4 kg and an average MUAC increase of 1.6 cm. Statistical analysis confirmed that these improvements were significant (p < 0.05). Additionally, participants showed increased knowledge and awareness of nutritious food consumption. The study concludes that the combination of nutrition education and locally sourced PMT is effective in improving the nutritional status of pregnant women with CED. Similar programs are recommended for replication in areas with high CED prevalence, with the active involvement of health cadres and the sustainable use of local food resources.